2017
DOI: 10.3168/jds.2016-12390
|View full text |Cite
|
Sign up to set email alerts
|

Only 7% of the variation in feed efficiency in veal calves can be predicted from variation in feeding motivation, digestion, metabolism, immunology, and behavioral traits in early life

Abstract: High interindividual variation in growth performance is commonly observed in veal calf production and appears to depend on milk replacer (MR) composition. Our first objective was to examine whether variation in growth performance in healthy veal calves can be predicted from early life characterization of these calves. Our second objective was to determine whether these predictions differ between calves that are fed a high- or low-lactose MR in later life. A total of 180 male Holstein-Friesian calves arrived at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(45 reference statements)
1
7
0
1
Order By: Relevance
“…In addition, ADG was not different between groups during the entire period (Table 2). It has been reported that RFI is repeatable within animal at different rearing phases, as the selection of animals based on RFI during the growth phase was predictive of the RFI rank of lactating cows and of veal calves (Gilbert at al., 2017). Furthermore, differences in gene expression associated with protein turnover and associated heat production in metabolically active tissues such as the liver and the gastrointestinal tract have been hypothesized as an alternative for increased understanding of the molecular mechanisms leading to variations in energy expenditure in cattle of similar BW and ADG (Nkrumah et al, 2006).…”
Section: Heat Production and Gas Exchangesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ADG was not different between groups during the entire period (Table 2). It has been reported that RFI is repeatable within animal at different rearing phases, as the selection of animals based on RFI during the growth phase was predictive of the RFI rank of lactating cows and of veal calves (Gilbert at al., 2017). Furthermore, differences in gene expression associated with protein turnover and associated heat production in metabolically active tissues such as the liver and the gastrointestinal tract have been hypothesized as an alternative for increased understanding of the molecular mechanisms leading to variations in energy expenditure in cattle of similar BW and ADG (Nkrumah et al, 2006).…”
Section: Heat Production and Gas Exchangesmentioning
confidence: 99%
“…Holstein heifer calves selected according to varying RFI during the growth phase presented divergences in RFI during the first lactation, even though the divergences were reduced at that time Gilbert et al, 2017). It has been observed that this variation in RFI has moderate heritability (h 2 = 0.45, Crowley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, their models did not include behavioral factors known to contribute to preweaning calf performance. For instance, Gilbert et al (2017) showed that drinking speed and fearfulness (response to human contact and Individual characteristics in early life relate to variability in weaning age, feeding behavior, and weight gain of dairy calves automatically weaned based on solid feed intake movement on a weigh scale) were negatively associated with weight gain in veal calves, and Neave et al (2018a) found that personality traits in dairy heifers (such as interactive, exploratory, and vocal responses when exposed to novel situations) were related to feeding behavior and performance before and during weaning. Behavioral measures in these studies were taken when calves were several weeks to several months of age; it is possible that other behaviors recorded at an early age may explain variability in feeding behavior, growth, and suitability to wean early.…”
Section: Introductionmentioning
confidence: 99%
“…Mean concentrations of NEFA tented to be greater in NC versus HRAS (P = 0.06) from birth to week 7 ( Figure 6), probably due to lower glucose levels. Concentrations of NEFA are sensitive to plasma glucose, and indicates greater mobilization of fat due to low nutrient intake (Abdelgadir et al, 1996;Zhang et al, 2010;Gilbert et al, 2017). Preweaning contrasts: NC versus HRTS (P = 0.12), NC versus HRAS (P = 0.05), MR versus WM (P = 0.14), TS versus AS (P = 0.62).…”
Section: Resultsmentioning
confidence: 99%